Improving Olive Leaf Phenolic Extraction with Pulsed Electric Field Technology Pre-Treatment - María del Carmen Razola-Díaz; Robert Sevenich; Oliver K. Schlüter; Vito Verardo; Ana María Gómez-Caravaca (Foods)
The olive leaf is one of the main by-products from the olive oil industry. This by-product is a rich source of phenolic compounds that have been shown to possess beneficial health activities, which are due in part to their antioxidant activities. Therefore, the revaluation of this by-product would be of great importance for the food industry. For this reason, this study focuses on the pretreatment of olive leaves with a technology based on the use of pulsed electric fields (PEF) and their following extraction by ultrasounds in order to obtain an extract enriched in phenolic compounds. A Box-Behnken design of 15 experiments with three independent factors has been carried out: electric field strength (kV/cm), frequency (Hz) and total treatment time (s). The response variables were the sum of phenolic compounds, hydroxytyrosol and oleuropein measured by HPLC-MS-ESI-TOF and the antioxidant activity measured by DPPH. The validity of the experimental design was confirmed by ANOVA and the optimal conditions were established by using the response surface methodology in combination with a desirability function. The PEF optimal conditions were 0.6 kV/cm at 90 Hz for 11 s, which allowed for obtaining an olive leaf extract with 26.8, 21.7 and 15.6% higher contents of hydroxytyrosol, oleuropein and total phenolic compounds, respectively, compared to the non-treated sample with PEF. The antioxidant activity measured by DPPH was increased significantly by 32.3%. The data confirmed that the pre-treatment with PEF under these optimal conditions has proven to be effective in improving the extraction of phenolic compounds in olive leaves.